2021
DOI: 10.37763/wr.1336-4561/66.6.933942
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Fire Hazard of Plywoods Using a Cone Calorimeter

Abstract: A high-efficiency fire retardant composition was prepared with dicyandiamide, phosphoric acid, boric acid, borax, urea and magnesium sulfate and it was used to process veneers which were then to prepare the plywood. Meanwhile, heat release and smoke release from combustion of plywood were tested by a cone calorimeter, including heat release rate, mass loss rate, CO yield, CO2 yield and oxygen consumption. Results showed that the plywood with this fire retardant treatment had the better flame-retardant performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…HRR refers to the heat released from per unit area of material combustion, reflecting the heat releasing rate of materials during combustion Figure a shows the HRR of the four samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRR refers to the heat released from per unit area of material combustion, reflecting the heat releasing rate of materials during combustion Figure a shows the HRR of the four samples.…”
Section: Resultsmentioning
confidence: 99%
“…HRR refers to the heat released from per unit area of material combustion, reflecting the heat releasing rate of materials during combustion. 26 Figure 9a shows the HRR of the four samples. It is observed that the HRR of the ROW sample shows a slowly increasing trend, but the HRR curve of the VOCs-adsorbed samples shows a rapid increase to the peak and then a rapid decrease.…”
Section: Heat Releasementioning
confidence: 99%